2015
DOI: 10.1002/pamm.201510225
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial shape functions on the logarithmic space: the LogFE method

Abstract: We extend the Logarithmic finite element method, a novel finite element approach for solving boundary-value problems proposed in [1], to a complete set of degrees of freedom, i.e. translational and rotational degrees of freedom in three dimensions. In contrast to the standard Ritz-Galerkin formulation, the shape functions are given on the logarithmic space of the deformation function. Unlike existing formulations based on Lie groups, they may include polynomial functions of arbitrary degree. The method focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…By elementary calculations, it can be shown that, for identical shape functions N I,r,q (ξ ) and initial configuration x 0 (ξ , η), the results of the action of g ξ := exp (ψ 1 (u)(ξ )) andg ξ := exp (ψ 2 (u)(ξ )) on the respective embeddings i 1 resp. i 2 of the initial configuration result in the same current configuration [25]. That is, we have…”
Section: Preliminary Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…By elementary calculations, it can be shown that, for identical shape functions N I,r,q (ξ ) and initial configuration x 0 (ξ , η), the results of the action of g ξ := exp (ψ 1 (u)(ξ )) andg ξ := exp (ψ 2 (u)(ξ )) on the respective embeddings i 1 resp. i 2 of the initial configuration result in the same current configuration [25]. That is, we have…”
Section: Preliminary Considerationsmentioning
confidence: 96%
“…Following the approach outlined in [24] and [25], we intend to present a formulation that includes, in addition to rotations and dilatations, the translations at the nodes of the configuration in a future publication.…”
Section: Introductionmentioning
confidence: 99%
“…In the Logarithmic finite element (LogFE) method, a novel finite element approach proposed by the authors [1,2], shape functions are defined on the Lie algebra of the deformation function, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With a suitable formulation, however, it is possible to ensure commutativity at relevant points on the border of a finite element, which is a precondition for achieving the desired linear relationship between such field variables and the set of global degrees of freedom. We refer to our previous contributions for details on the explicit formulation of the Logarithmic finite element method, including an implementation for a planar Bernoulli beam element [1,2].…”
Section: Formulationmentioning
confidence: 99%
“…The Logarithmic finite element ("LogFE") method [1][2][3] provides a smooth interpolation of the field variables on the coarse grid. It thus minimizes spurious high-frequency components on the fine grid and can avoid locking phenomena associated with the use of linear interpolation.…”
Section: Motivationmentioning
confidence: 99%